2015
DOI: 10.3390/nu7125542
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in Early Life: A Key Element in the Fetus and Preterm Neonate

Abstract: Zinc is a key element for growth and development. In this narrative review, we focus on the role of dietary zinc in early life (including embryo, fetus and preterm neonate), analyzing consequences of zinc deficiency and adequacy of current recommendations on dietary zinc. We performed a systematic search of articles on the role of zinc in early life. We selected and analyzed 81 studies. Results of this analysis showed that preservation of zinc balance is of critical importance for the avoidance of possible con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 128 publications
(216 reference statements)
1
153
0
5
Order By: Relevance
“…Adjustment for these factors did not change the effect estimates materially. Several trials suggested that supplementation with these micronutrients lowers the risk of pregnancy complications in women at risk of deficiencies or adverse outcomes (50)(51)(52)(53)(54)(55). Because the intake of these micronutrients was estimated from a food-frequency questionnaire, we may not have achieved the precision in these concentrations compared with studies with concentrations available.…”
Section: Discussionmentioning
confidence: 98%
“…Adjustment for these factors did not change the effect estimates materially. Several trials suggested that supplementation with these micronutrients lowers the risk of pregnancy complications in women at risk of deficiencies or adverse outcomes (50)(51)(52)(53)(54)(55). Because the intake of these micronutrients was estimated from a food-frequency questionnaire, we may not have achieved the precision in these concentrations compared with studies with concentrations available.…”
Section: Discussionmentioning
confidence: 98%
“…Pregnant women who are vegans or vegetarians need specific counselling because vegans always require supplementation of vitamin B 12 and possibly additional nutrients, and also vegetarians should consider improving the intake of critical micronutrients [17]. Moreover, women at risk of gastrointestinal mal-absorption are candidates for zinc supplementation [43]. Although international guidelines support the supplementation of folic acid and other micronutrients (e.g., [44]), most of the current guidance for pregnant women and for young children does not take into account the long-term programming consequences of early nutrition [16].…”
Section: Micronutrient Supply During Pregnancymentioning
confidence: 99%
“…Selenium is a cofactor of 5-iodothyronine deiodinase, which determines the proper function of key antioxidant enzymes deiodinase and glutathione peroxidase [22]. Pregnant women require 60 µg/day of selenium.…”
Section: Seleniummentioning
confidence: 99%